Analisa Strategi Peningkatan Pendapatan Zakat, Infaq dan Sedekah di Kota Batam di Era Perkembangan Teknologi Digitalisasi - Adiyanto, Adiyanto; Widana, Gusti Oka (Jurnal Ilmiah Ekonomi Islam, 2024)
This study aims to examine strategies to improve Zakat, Infaq, and Sadaqah (ZIS) collection in the city of Batam in the era of digital technology development. Given Batam's rapid growth and the huge potential of an industrial workforce that largely uses digital technology, this study identifies opportunities and challenges in ZIS collection. Descriptive qualitative method was used, with data collected through interviews and literature study. The research findings show that although Baznas Kota Batam has strengths in terms of management and excellent programs, there are still weaknesses in optimizing the potential of ZIS collection. Recommended strategies include strengthening digitalization efforts, improving zakat literacy, and collaborating with various stakeholders to expand the reach of ZIS collection. This research aims to contribute to the development of more effective zakat collection strategies in the digital era.